2021
DOI: 10.3390/cells10123409
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Epigenetic Patterns Related to DNA Replication in Vicia faba Root Meristem Cells under Cadmium-Induced Stress Conditions

Abstract: Experiments on Vicia faba root meristem cells exposed to 150 µM cadmium chloride (CdCl2) were undertaken to analyse epigenetic changes, mainly with respect to DNA replication stress. Histone modifications examined by means of immunofluorescence labeling included: (1) acetylation of histone H3 on lysine 56 (H3K56Ac), involved in transcription, S phase, and response to DNA damage during DNA biosynthesis; (2) dimethylation of histone H3 on lysine 79 (H3K79Me2), correlated with the replication initiation; (3) phos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 76 publications
(107 reference statements)
2
6
0
Order By: Relevance
“…Using the iPOND method, a strong H3K56Ac band in both control and HU-treated cells was observed, clearly demonstrating the validity of the applied technique, but we did not find increased levels of H3K56 acetylation on newly deposited histones after HU treatment. In contrast, immunocytochemical studies showed that, compared to untreated material, HU-treated cells displayed a significant increase in the mean number of intranuclear foci, which is consistent with our previous studies using CdCl 2 -induced replication stress (Żabka et al 2021a ). Thus, the results obtained with these methods appear to be good indicators of DNA damage and support the theory of Masumoto et al (Masumoto et al 2005 ) that cells with DNA strand breaks maintain high levels of H3K56 acetylation and that the maintenance of this modification depends on DNA damage checkpoint proteins, creating favorable chromatin environment for DNA repair.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Using the iPOND method, a strong H3K56Ac band in both control and HU-treated cells was observed, clearly demonstrating the validity of the applied technique, but we did not find increased levels of H3K56 acetylation on newly deposited histones after HU treatment. In contrast, immunocytochemical studies showed that, compared to untreated material, HU-treated cells displayed a significant increase in the mean number of intranuclear foci, which is consistent with our previous studies using CdCl 2 -induced replication stress (Żabka et al 2021a ). Thus, the results obtained with these methods appear to be good indicators of DNA damage and support the theory of Masumoto et al (Masumoto et al 2005 ) that cells with DNA strand breaks maintain high levels of H3K56 acetylation and that the maintenance of this modification depends on DNA damage checkpoint proteins, creating favorable chromatin environment for DNA repair.…”
Section: Discussionsupporting
confidence: 91%
“…Since, more recently, our research has focused on RS and epigenetic modifications after cadmium treatment (Żabka et al 2021a , b ), we, therefore, began to search for a more sensitive method that would allow the analysis of post-translational histone modifications in active and inhibited or damaged RFs. Our attention and interest was drawn to a technique called iPOND (isolation of proteins on nascent DNA), first published in 2011 by Sirbu et al ( 2011 ), which provides a high-resolution spatial–temporal analysis of proteins in RFs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Metal impact on histone modifications is relatively less well studied, however on-essential metals were shown to modulate expression of gene’s associated with histone biosynthesis and modifications on the transcriptional and post-transcriptional levels ( Cao et al., 2014 , Deckert and Sobkowiak, 2006 , Imran et al., 2019 ; Imran et al., 2020 ; Shafiq et al., 2020 ). Conseuquenlty, also the pattern of histone modifications (methylation and acetylation) was modulated by the metals ( Żabka et al., 2021 ). Epitranscriptomic changes are relatively new players in the field of plant stress biology.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment with Cd caused increases abundance of transcripts encoding KYP, IBM1 and HDA8 in A. halleri PL22 population but decreased abundance in the I16 population ( Galati et al., 2021 ). Changes in histone modifications were also evidenced by immunofluorescence techniques in root meristem cells of broad bean ( Vicia faba ) ( Żabka et al., 2021 ). Decreased demethylation of histone 3 at lysine 79 (H3K79Me2), which is associated with replication initiation events, was observed in Cd-treated plants in relation to the control in all three analyzed cell cycle phases (G1, S and G2).…”
Section: Histone Modificationsmentioning
confidence: 99%